Generating Random Variables that follow the Beta Distribution Using the Neutrosophic Acceptance-Rejection Method - Maissam Jdid; Nada A. Nabeeh (Neutrosophic Sets and Systems, 2023)
Analysis using simulation is a natural and logical extension of the analytical and mathematical models inherent in operations research. Simulation has become a modern tool that helps in studying many systems that we could not study or predict the results that we could obtain during the operation of these systems over time before the existence of Simulation, since the main interest in statistical analysis is to obtain a series of random variables that follow the probability distribution in which the system under study operates, through a series of random numbers that follow a uniform distribution over the domain [0, 1], using scientific methods provided by the efforts of researchers. In the field of modeling and simulation, such as the reverse transformation method, the rejection and acceptance method, and other methods that we have reformulated using the concepts of neutrosophic science in previous research. In summary of what we have done previously, we present in this research a study whose purpose is to generate random variables that follow the beta distribution, which is used in many applications. In administrative processes, especially in analyzing network diagrams using the neutrosophic rejection and acceptance method.